JUDI ONLINE DAN KONTROL SOSIAL MASYARAKAT PEDESAAN - Rina Susanti (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
In 2020, 14,726 gambling content was found to target rural communities including children, teenagers, and adults. The purpose of the study was to analyze the impact and the control of people over Ding Dong Live gambling using Hirschi theory. The research took place in Tanjung Sawah Kampar Utara Village using qualitative research through observation, interview and documentation being the techniques of collecting data. The results showed the impact of Live Ding Dong's online gambling activities, namely domestic disputes, disputes between citizens, theft, and the anxiety of parents who worry about their children doing similar gambling. The controls can be reprimanding landowners and stalls that provide gambling venues and bookies, putting up gambling hazard banners, and employing religious lectures to give advice. Control is ineffective primarily on the application of functions and the role of families and formal elements in the study area. The most fundamental cause of weak social control is that there is still a kinship relationship between players or gamblers and local community so that when there is family reporting, it will bear shame and social sanctions. Therefore, awareness, enforcement, and coaching from local influential figures, especially public figures and formal figures are required to provide legal awareness of the Live Ding Dong online gambling issue.